Последний год Достоевского: исторические. записки / И. Л. Волгин - Волгин Игорь Леонидович (Советский писатель, 1991)
Экземпляры: аб. (1991) / Инвентарный номер: 34551 / Цена: / Сис.шифр: 83.3(2=Рус)5-8 / Авт.знак: В 67 / ГРНТИ: 17.09.91 / ББК: 83.3(2=Рус)5-8 Достоевский